Transparency in Financial and Fiscal Affairs at Municipal Level: The Lessons from the Gandaki Province, Nepal - Silwal, Sudarshan (Dhaulagiri Journal of Contemporary Issues, 2023)
This article examines the transparency in financial and fiscal affairs at municipal level in terms of tax revenue misuse, allocation of resources, information on tax revenue collection, local tax system, decision making process, stakeholder engagement, mechanism for public participation, delivery of vital public services, local budget, tax and fees collection procedure, financial allocation and audited statement of municipal revenue and expenditure related information posted in the public places. Descriptive method and purposive sampling procedure were adopted to carry out this study. It is found that majority of the respondents believed that there are misuses of tax revenue; the policy involved in rising for municipal resource mobilization has been found positive but it has to restructure and re-improve as per the time frame; majority of the respondents were found known about the local budget and tax and fees/fines collection procedure but a few respondents were familiar with financial allocation to sectors; almost all the respondents pointed out to municipal authorities to be punished for the reduction of municipal tax. Finally, summarizing the results and discussions pertaining to these issue sit can be said that there is miscellaneous response and less transparency in financial and fiscal affairs. It is necessary to focus on improving information dissemination at public places. Promoting citizen participation in developmental activities, strengthening institutional capacity, building public trust in local governance and creating the harmonization of existing policy concerning to the municipal government effectively can enhance transparency and accountability in municipalities.